Is Face-to-Face Learning Better than Online Learning? Teachers’ voice on the Use of Google Workspace - Nuraeni Nuraeni (Institut Agama Islam Negeri Palopo, 2021)
The study focused on teachers’ voices on the use of Google Workspace (G-Workspace) for education amidst the pandemic. The objects of the study were seven participants. All the participants were teachers at Universitas Muslim Maros. The data was collected using a structured interview. The collected data was analysed using Miles and Huberman’s analysis. The result showed that from the perspectives of teachers, G-Workspace had been used as a group of applications to portray the real offline classroom. The most used applications were G-classroom, G-Meet and G-Mail. Unfortunately, there were some unpopular applications such as G-Calendar and G-Jamborad. G-Workspace promotes integrated applications and collaborative learning. From the result, the integration of the applications gave advantages to the participants as they could open some applications through G-Classroom. Meanwhile, working collaboratively was not the best option as the result of the lack of knowledge on collaborative online learning as well as the incompatible device from students. Notwithstanding, G-Workspace had helped most participants to achieve their learning objectives and they referred to it as helpful applications for learning. However, some participants believed that even though G-Workspace had been a medium for distance learning, they were not able to ensure students’ understanding of the material. Therefore, they chose face-to-face learning as the best way to deliver the teaching material